Native and Non-Native Accents of English: Different Perceptions of English as a Global Language in a Phonetic Perspective. An Editorial to RiL Special Issue Vol. 20.1 and 20.2. - Jarosz , Anna; Witczak-Plisiecka , Iwona (Research in Language, 2022)
The text reviews selected current issues related to native and non-native accents of English, including the status of English as a global language, the value of varieties of English and the question of a possible supremacy of one accent over other varieties. The text links theoretical and applied issues addressing the question of which variety should be used in EFL education. Focusing on the phonetic dimension it weights the conflicting reasons given in classic works, such as Kachru’s and McArthur’s to eventually point to novel research programmes as exemplified in other texts included in the special issues of Research in Language, i.e. vol. 20, issues 1 and 2, most of which were inspired by Accents 2021, an annual conference organised by the Department of English Language and Applied Linguistics, Institute of English Studies, University of Lodz, Poland.